Assessment of the menstrual cycle, eating disorders and self-esteem of Polish adolescents - Agnieszka Drosdzol-Cop; Monika Bąk-Sosnowska; Dominika Sajdak; Agnieszka Białka; Agnieszka Kobiołka; Grzegorz Franik; Violetta Skrzypulec-Plinta (Taylor & Francis Group, 2017)
Introduction: Eating disorders are an important factor in menstrual cycle disorders in girls. Moreover, low self-esteem among adolescent girls may be a risk factor for eating disorders. The aim of the study was to assess the menstrual cycle, eating habits and self-esteem of Polish adolescents. Methods: The study was conducted from January 2014 to March 2015 and included 623 girls, aged 15-19, from randomly selected junior high schools in Silesia, Poland, in which their menstrual cycle, risk of eating disorders and self-esteem were evaluated. A five-part questionnaire was used to assess basic demographic data, lifestyle and physical activity, gynecological history, as well as Rosenberg Self-Esteem Scale (SES) and Eating Attitude Test (EAT-26). Results: Irregular menstrual cycles were observed in 236 (37.88%) girls; 5.20% presented secondary amenorrhea. Based on the EAT-26 test, 101 (16.21%) girls were indicated being at risk for an eating disorder. Low self-esteem was observed in 340 (54.57%) study girls on the base of SES. Discussion: Girls with irregular menses had higher scores on the EAT-26 test in subscales: EAT-overall score, EAT-diet and EAT-bulimia, while lower scores on the SES. In our study, we did not observe a significant relationship between exercise intensity, body mass, BMI and menstrual cycle regularity. Low self-esteem among adolescent girls may be a risk factor for eating disorders which could interrupt the menstrual cycle.